Sub-Acute Treatment of Curcumin Derivative J147 Ameliorates Depression-Like Behavior Through 5-HT1A-Mediated cAMP Signaling - Li, Jianxin; Chen, Ling; Li, Gaowen; Chen, Xiaojuan; Hu, Sisi; Zheng, Liang; Luria, Victor; Lv, Jinpeng; Sun, Yindi; Xu, Ying; Yu, Yingcong (Frontiers in Neuroscience, 2020)
Background: Major depressive disorder (MDD) is a severe mental disorder related to the deficiency of monoamine neurotransmitters, particularly to abnormalities of 5-HT (5-hydroxytryptamine, serotonin) and its receptors. Our previous study suggested that acute treatment with a novel curcumin derivative J147 exhibited antidepressant-like effects by increasing brain derived neurotrophic factor (BDNF) level in the hippocampus of mice. The present study expanded upon our previous findings and investigated the antidepressant-like effects of sub-acute treatment of J147 for 3 days in male ICR mice and its possible relevancy to 5-HT1A and 5-HT1B receptors and downstream cAMP-BDNF signaling. Methods: J147 at doses of 1, 3 and 9 mg/kg (via gavage) was administered for 3 days and the anti-immobility time in the forced swimming and tail suspension tests (FST and TST) was recorded. The radioligand binding assay was used to determine the affinity of J147 to 5-HT1A and 5-HT1B receptor. Moreover, 5-HT1A or 5-HT1B agonist or its antagonist was used to determine which 5-HT receptor subtype is involved in the antidepressant-like effects of J147. The downstream signaling molecules such as cAMP, PKA, pCREB and BDNF were also measured to determine the mechanism of action. Results: The results demonstrated that sub-acute treatment of J147 remarkably decreased the immobility time in both the FST and TST in a dose-dependent manner. J147 displayed high affinity in vitro to 5-HT1A receptor prepared from mice cortical tissue and was less potent at 5-HT1B receptor. These effects of J147 were blocked by pretreatment with a 5-HT1A antagonist NAD-299 and enhanced by a 5-HT1A agonist 8-OH-DPAT. However, 5-HT1B receptor antagonist NAS-181 did not appreciably alter the effects of J147 on depression-like behaviors. Moreover, pretreatment with NAD-299 blocked J147-induced increases in cAMP, PKA, pCREB and BDNF expression in the hippocampus. While 8-OH-DPAT enhanced the effects of J147 on these proteins’ expression. Conclusion: The results suggest that J147 induces rapid antidepressant-like effects during a 3-day treatment period without inducing drug tolerance. These effects might be mediated by 5-HT1A dependent cAMP/PKA/pCREB/BDNF signaling.